2016
DOI: 10.26719/2016.22.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Relative inequalities in geographic distribution of health care resources in Kermanshah province, Islamic Republic of Iran

Abstract: This study aimed to evaluate inequalities in the geographical distribution of human and physical resources in the health sector of Kermanshah province, Islamic Republic of Iran. In a retrospective, cross-sectional study, data from the Statistical Centre of Iran were used to calculate inequality measures (Gini coefficient and index of dissimilarity) over the years 2005-11. The highest Gini coefficient for human resources was observed for pharmacists in 2005 (0.75) and the lowest for paramedics in 2010 and 2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…[ 26 ] However, other evidences show that, with an increase in the specialization and education of human resources in health-care sector, inequality in their distribution increases. [ 22 27 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 26 ] However, other evidences show that, with an increase in the specialization and education of human resources in health-care sector, inequality in their distribution increases. [ 22 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Based on various evidences, it is possible to conclude that inequality in health care is high and in provinces such as Tehran and Kermanshah, there are large inequalities in distribution of GPs. [ 27 28 ] The study by Mobaraki et al . showed lower inequality in distribution of resources in public sector in medical science universities.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, the previous studies have shown different and somewhat mixed and inconsistent results in terms of resources distribution, especially human resources. Some studies displayed inequitable status in terms of various resources distribution in such provinces as Ardabil (32), Lorestan (33) and Kermanshah (34).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the geographical distribution of human resources has been studied in several studies in Iran (3,18). The trend of human resource development in Iran has shown a significant increase over the past three decades, but their distribution does not seem to be fair (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%